Wage inequality in a developing open economy: Portugal, 1944–1984 - Lains, Pedro (2016)
This paper estimates and analyses wage inequality trends in Portugal, from 1944 to 1984, a period that comprises the Estado Novo dictatorship and the first decade after the transition to democracy. Wage inequality is measured by the gap between skilled and unskilled labour, and reveals a downward trend in most of the period in analysis. We provide an explanation for the observed trends by looking at the influence of domestic and international forces on changes in the relative supply and demand of skilled labour. According to our findings, the skill premium declined due to the combined influence of two major forces: an increase in the relative supply of skilled labour due to the mass emigration of unskilled labour, and the decrease in the relative demand for skills, related to trade-induced changes stemming from the country's increasing openness, which followed the country's unskilled labour comparative advantages. Our findings point to the conclusion that the impact of openness on wage inequality is related to the country's relative level of development among its major trading partners.